Tuberculous Parotid Abscess in an 11-Year-Old Girl - Haque, Md Mozammel; Shultana, Kamrunnaher; Afroza, Syeda (Journal of Bangladesh College of Physicians and Surgeons, 2018)
This case is being reported because tubercular involvement of the parotid gland in the pediatric population is extremely rare even in the TB endemic country like Bangladesh. Here, a case of an 11 year old girl with tuberculous abscess of the right parotid gland is reported who presented with right sided earache, headache and fever for two months followed by development of a swelling in front of the right ear for one and half months. There was no history of running nose, drooling of saliva, pain on deglutition, prolonged cough or hemoptysis, loss of appetite or weight loss. Patient came from an area where many known TB patients reside. General and systemic examination revealed no abnormality except the swelling. Her BCG mark was present and BMI was age appropriate. Tuberculin test (MT) was positive and chest x-ray revealed no abnormality. The diagnosis of tuberculous parotid abscess was initially made by histopathology of the swelling. Treatment was commenced with a six months anti-TB regimen according to the national TB guideline. Finally, TB was confirmed upon the clinical response to anti-TB therapy. Therefore, it is recommended to consider TB in the differential diagnosis of parotiditis and chronic swelling of this salivary gland especially in TB endemic countries. J Bangladesh Coll Phys Surg 2019; 37(1): 39-42